Technology and problem-based learning - Uden, Lorna; Beaumont, Chris (Hershey, PA : Information Science Pub., 2006)
Aimed at educators who may be considering introducing Problem-based Learning (PBL) and need to know what it involves, its benefits, and the details of how to implement it. This book also covers major issues, including rationale for PBL, how to write effective problems, preparing students and tutors, being an effective facilitator, and more.
Includes bibliographical references and index.
Keywords: Problem-based learning; Educational technology; EDUCATION -- Experimental Methods